EVALUASI PROGRAM INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) DI BATU CERMIN RT 06 KELURAHAN SEMPAJA UTARA KECAMATAN SAMARINDA UTARA - Santi Rande (Jurnal Paradigma (JP), 2017)
This research aims to find out and analyze the impact of waste water management  installation at Batu Cermin RT 06 Sempaja, Samarinda Utara Sub-District as well as analyzing hindering factors of the program. As for the result, it can be said that the waste water management installation program in Batu Cermin in overall summary has been deployed quite well even though there are some things that could be upgraded to increase the optimalization of the program